Effects of aquifer size and formation fracture pressure on CO2 geological storage capacity - Jung, Seungpil; Lee, Kyungbook (Frontiers in Energy Research, 2024)
Introduction: Carbon capture and storage (CCS) is important for achieving net-zero carbon emissions. However, although the current geological storage capacity stands at approximately 3,000 Gt-CO2, the formation pressure increases with CO2 injection, imposing severe constraints on capacity from a geomechanical perspective. This study numerically examined nine cases (combinations of three fracture pressures and three aquifer radius factors) through sensitivity analysis to quantify the effects of these parameters on CO2 injection mass and storage capacity. Methods: The CO2 injection mass was determined as the cumulative CO2 injected until the formation pressure reached a specified fracture pressure. Storage capacity was defined as the amount of CO2 enclosed within the reservoir based on a fill-and-spill analysis encompassing 200 years after the start of injection (2230). Results: Based on the sensitivity analysis, the aquifer radius had a greater impact on the CO2 injection mass and storage capacity than the fracture pressure. A sufficiently high aquifer radius factor can compensate for the capacity limitations imposed by a low fracture pressure. For the lowest fracture pressure (20.95 MPa), considering a safety factor of 0.8, the CO2 injection mass increased approximately 5.5 times, from 3.2 to 17.6 Mt-CO2, depending on the aquifer radius factor ranging from 2 to 7. Discussion: Therefore, geological sites with high aquifer radius factors and low fracture pressures were preferred over those with low aquifer radius factors and high fracture pressures. Nevertheless, when considering space-limited capacity, storage efficiency, defined as the ratio of injected to stored CO2, tends to be higher (approximately 80%) when both parameters are low. The scenario featuring the highest aquifer radius factor and fracture pressure reached an injection mass of 68.9 Mt-CO2. However, the storage efficiency was only 23% due to space constraints. This study provides key insights into two pivotal parameters from pressure- and space-limited perspectives, which must be collectively considered to reliably evaluate CCS projects.